Defect state titanium dioxide supported catalyst, method of making and use in co-conversion of methane and carbon dioxide

CN119098168BActive Publication Date: 2026-10-27UNIV OF SCI & TECH OF CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411282824.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2026-10-27
Estimated Expiration
2044-09-12

AI Technical Summary

Technical Problem

然而,由于CH4和CO2都是高度对称的非极性分子,热催化CH4和CO2共转化往往需要苛刻的高温高压条件,这容易引发许多副反应,例如积碳

Benefits of technology

[0029]本发明通过将缺陷态二氧化钛纳米片作为载体,负载金属颗粒(Au)后,金属颗粒作为光生电子的捕获中心,促进光生电子-空穴对的空间分离。另外形成的金属-载体界面位点有效增强了光催化剂对于CH4和CO2的吸附和激活。并且,负载的高电负性金属Au还可以作为甲基的耦合位点,因此获得了高产率的C2H6,同时得到相应的CO产物。经研究,缺陷二氧化钛纳米片负载的Au量子点在温和条件下光催化共转化CH4和CO2的反应中,获得了2.6mmol g-1的乙烷产率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119098168B_ABST
    Figure CN119098168B_ABST
Patent Text Reader

Abstract

The present application relates to the field of photocatalysis, and particularly relates to a defect-state titanium dioxide supported catalyst, a preparation method and application of the defect-state titanium dioxide supported catalyst in a co-conversion of methane and carbon dioxide reaction. The defect-state titanium dioxide supported catalyst comprises a carrier and metal Au supported on the surface of the carrier; and the carrier is a defect-state titanium dioxide nanosheet with oxygen vacancies. In the present application, the defect-state titanium dioxide nanosheet is used as a carrier, and metal particles (Au) are supported on the carrier. The metal particles act as a capture center of photo-generated electrons, and promote the spatial separation of photo-generated electron-hole pairs. In addition, the metal-carrier interface sites formed effectively enhance the adsorption and activation of the photocatalyst for CH4 and CO2. Furthermore, the supported high-electronegativity metal Au can also act as a coupling site of methyl, so that a high yield of C2H6 is obtained, and a corresponding CO product is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photocatalysis technology, and in particular to a defect-state titanium dioxide supported catalyst, its preparation method, and its application in the co-conversion reaction of methane and carbon dioxide. Background Technology

[0002] Methane and carbon dioxide are the two main greenhouse gases, accounting for approximately 90% of global emissions. They are also recognized as C1 feedstocks for fuels with high bond energy used in the production of high-value chemicals. Ethane is a component of natural gas and petroleum and plays a vital role in modern society. Furthermore, ethane is a feedstock for ethylene production, and a significant portion of global plastics production relies on ethylene; therefore, ethane supply directly impacts the plastics and related industries. The co-conversion of CH4 and CO2 to ethane not only helps mitigate the increasingly severe greenhouse effect but also helps meet the rapidly growing demand for ethane. However, because both CH4 and CO2 are highly symmetrical nonpolar molecules, the thermocatalytic co-conversion of CH4 and CO2 often requires harsh high-temperature and high-pressure conditions, which can easily trigger many side reactions, such as carbon deposition. Additionally, the thermocatalytic co-conversion of CH4 and CO2 often results in syngas products, which require additional Fischer-Tropsch reactions to be converted into high-value chemicals. Summary of the Invention

[0003] In view of this, the technical problem to be solved by the present invention is to provide a defect-state titanium dioxide supported catalyst, a preparation method thereof, and its application in the co-conversion reaction of methane and carbon dioxide. The prepared defect-state titanium dioxide supported catalyst can catalyze the co-conversion of methane and carbon dioxide into ethane.

[0004] This invention provides a defect-state titanium dioxide supported catalyst, comprising a support and metallic Au supported on the surface of the support;

[0005] The carrier is a defective titanium dioxide nanosheet with oxygen vacancies.

[0006] Preferably, the loading of the metal Au is 1% to 3%.

[0007] Preferably, the thickness of the defect-state titanium dioxide nanosheets is 3~5 nm;

[0008] The average particle size of the metal Au is 1~8 nm.

[0009] This invention provides a method for preparing the above-mentioned defect-state titanium dioxide supported catalyst, comprising the following steps:

[0010] S1) Titanium dioxide nanosheets and a salt solution of metallic gold are mixed, and the solvent is removed to obtain a mixed powder;

[0011] S2) The above mixed powder is calcined under a hydrogen-argon atmosphere to obtain a defect-state titanium dioxide supported catalyst.

[0012] Preferably, the titanium dioxide nanosheets are prepared according to the following method:

[0013] Titanium dioxide nanosheets were obtained by mixing a titanium source compound and an acidic compound and carrying out a hydrothermal reaction.

[0014] Preferably, the titanium source compound includes tetrabutyl titanate;

[0015] The acidic compound includes hydrofluoric acid;

[0016] The hydrothermal reaction temperature is 160~200℃; the hydrothermal reaction time is 12~24h.

[0017] Preferably, the salt solution of metallic gold includes one or more of HAuCl4 solution and NaAuCl4 solution;

[0018] The roasting temperature is 300~500℃; the roasting time is 1~2 hours;

[0019] The heating rate of the calcination is 2~10 ℃ / min;

[0020] The hydrogen-argon atmosphere is a mixture of hydrogen and argon, with a hydrogen volume content of 2% to 20%.

[0021] This invention provides the application of the above-mentioned defective titanium dioxide supported catalyst or the defective titanium dioxide supported catalyst prepared by the above preparation method as a catalyst for the co-conversion of methane and carbon dioxide.

[0022] This invention provides a method for co-converting methane and carbon dioxide, comprising the following steps:

[0023] The defective titanium dioxide supported catalyst described above or the defective titanium dioxide supported catalyst prepared by the above preparation method catalyzes the photocatalytic reaction of methane and carbon dioxide to obtain ethane and carbon monoxide.

[0024] Preferably, the light source for the photoreaction is selected from any one of xenon lamps, high-pressure mercury lamps, LED lamps, or tungsten iodine lamps;

[0025] The power of the light source in the photoluminescence reaction is 100-1000 mW / cm². -2 ;

[0026] The photoreaction time is 0.5~4 h;

[0027] The volume ratio of methane to carbon dioxide is 1:19 to 19:1.

[0028] Compared with the prior art, the present invention achieves the following beneficial effects:

[0029] This invention utilizes defective titanium dioxide nanosheets as a support to load metal particles (Au). The metal particles act as trapping centers for photogenerated electrons, promoting spatial separation of photogenerated electron-hole pairs. Furthermore, the resulting metal-support interface sites effectively enhance the adsorption and activation of CH4 and CO2 by the photocatalyst. Moreover, the highly electronegative Au loaded on the nanosheets can also serve as coupling sites for methyl groups, thus yielding high-yield C2H6 while simultaneously producing the corresponding CO product. Studies have shown that Au quantum dots supported on defective titanium dioxide nanosheets, under mild conditions, yielded 2.6 mmol g of the photocatalytic co-conversion of CH4 and CO2. -1 ethane yield. Attached Figure Description

[0030] Figure 1 The TiO2 nanosheets prepared in Comparative Example 1, the Au / TiO2 nanosheets prepared in Comparative Example 2, and the Au / TiO2-V nanosheets prepared in Example 1 are shown. o XRD pattern of nanosheets;

[0031] Figure 2 The Au / TiO2-V prepared in Example 1 o STEM images and particle size distribution of nanosheets;

[0032] Figure 3 The Au / TiO2-V prepared in Example 1 o Elemental distribution diagram of nanosheets;

[0033] Figure 4 The TiO2 nanosheets prepared in Comparative Example 1, the Au / TiO2 nanosheets prepared in Comparative Example 2, and the Au / TiO2-V nanosheets prepared in Example 1 are shown. o XPS spectra of nanosheets;

[0034] Figure 5 The TiO2 nanosheets prepared in Comparative Example 1, the Au / TiO2 nanosheets prepared in Comparative Example 2, and the Au / TiO2-V nanosheets prepared in Example 1 are shown. o EPR spectrum of nanosheets;

[0035] Figure 6 The Au / TiO2-V prepared in Example 1 o AFM images of nanosheets and corresponding height distribution maps;

[0036] Figure 7 TEM images of the TiO2 nanosheets prepared in Comparative Example 1 and the Au / TiO2 nanosheets prepared in Comparative Example 2;

[0037] Figure 8 HRTEM image of the TiO2 nanosheets prepared in Comparative Example 1;

[0038] Figure 9 The Au / TiO2 nanosheets prepared in Comparative Example 2 and the Au / TiO2-V nanosheets prepared in Example 1 are examples of the Au / TiO2 nanosheets prepared in Comparative Example 2 and the Au / TiO2-V nanosheets prepared in Example 1. o Comparison of static photocurrent tests on nanosheets;

[0039] Figure 10 The Au / TiO2 nanosheets prepared in Comparative Example 2 and the Au / TiO2-V nanosheets prepared in Example 1 are examples of the Au / TiO2 nanosheets prepared in Comparative Example 2 and the Au / TiO2-V nanosheets prepared in Example 1. o Comparison of surface photovoltage tests on nanosheets;

[0040] Figure 11 The Au / TiO2 nanosheets prepared in Comparative Example 2 and the Au / TiO2-V nanosheets prepared in Example 1 are examples of the Au / TiO2 nanosheets prepared in Comparative Example 2 and the Au / TiO2-V nanosheets prepared in Example 1. o Comparison of photoluminescence tests on nanosheets;

[0041] Figure 12 The TiO2 nanosheets prepared in Comparative Example 1, the Au / TiO2 nanosheets prepared in Comparative Example 2, and the Au / TiO2-V nanosheets prepared in Example 1 are shown. o UV-vis spectrum of nanosheets;

[0042] Figure 13 The Au / TiO2 nanosheets prepared in Comparative Example 2 and the Au / TiO2-V nanosheets prepared in Example 1 are examples of the Au / TiO2 nanosheets prepared in Comparative Example 2 and the Au / TiO2-V nanosheets prepared in Example 1. o CO2-TPD spectrum of nanosheets;

[0043] Figure 14 The Au / TiO2 nanosheets prepared in Comparative Example 2 and the Au / TiO2-V nanosheets prepared in Example 1 are examples of the Au / TiO2 nanosheets prepared in Comparative Example 2 and the Au / TiO2-V nanosheets prepared in Example 1. o CH4-TPD spectrum of nanosheets;

[0044] Figure 15 The Au / TiO2 nanosheets prepared in Comparative Example 2 and the Au / TiO2-V nanosheets prepared in Example 1 are examples of the Au / TiO2 nanosheets prepared in Comparative Example 2 and the Au / TiO2-V nanosheets prepared in Example 1. o CO2 adsorption energy diagram of nanosheets;

[0045] Figure 16 The TiO2 nanosheets prepared in Comparative Example 1, the Au / TiO2 nanosheets prepared in Comparative Example 2, and the Au / TiO2-V nanosheets prepared in Example 1 are shown. o Product distribution diagram of photocatalytic co-conversion of CH4 and CO2 by nanosheets;

[0046] Figure 17 The Au / TiO2-V prepared in Example 1 oPrecipitation rates of C2H6 under different Au mass fractions loaded on nanosheets;

[0047] Figure 18 The Au / TiO2-V prepared in Example 1 o Synchrotron radiation ultraviolet photoionization mass spectra of isotope-labeled experiments of photocatalytic co-conversion of CH4 and CO2 using nanosheets. Detailed Implementation

[0048] This invention provides a defect-state titanium dioxide supported catalyst, comprising a support and metallic Au supported on the surface of the support;

[0049] The carrier is a defective titanium dioxide nanosheet with oxygen vacancies.

[0050] Preferably, the loading of the metal Au is 1% to 3%. Experimental results show that controlling the Au loading to 1% to 3% can yield C2H6 products with a higher precipitation rate.

[0051] Preferably, the thickness of the defective titanium dioxide nanosheets is 3-5 nm; including but not limited to 3 nm, 3.1 nm, 3.2 nm, 3.3 nm, 3.4 nm, 3.5 nm, 3.6 nm, 3.7 nm, 3.8 nm, 3.9 nm, 4.0 nm, 4.1 nm, 4.2 nm, 4.3 nm, 4.4 nm, 4.5 nm, 4.6 nm, 4.7 nm, 4.8 nm, 4.9 nm, or 5 nm. The defective titanium dioxide nanosheets exhibit excellent photosensitivity, and the abundant defect sites on the nanosheets can adjust the electronic and band structures of the titanium dioxide nanosheets, serving as active sites for reactant adsorption. Controlling its thickness to 3-5 nm can effectively shorten the transport distance of photogenerated carriers, improve the separation efficiency of photogenerated electron-hole pairs, and thus enhance catalytic performance. In this invention, if the particle size of the loaded metal Au particles is too large, it will cover the surface of the defective titanium dioxide nanosheets, reduce the adsorption sites in the subsequent actual photocatalysis, and intensify electron-hole recombination, resulting in a decrease in catalytic performance. Conversely, if the particle size is too small, it means that the amount of loaded metal is too low, which will also lead to poor catalytic performance. Therefore, in this invention, the average particle size of the metal Au particles is preferably 1~8 nm, including but not limited to 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm or 8 nm.

[0052] While single titanium dioxide nanosheets exhibit good photosensitivity, they also suffer from high rebinding efficiency of photogenerated carriers. This invention promotes spatial separation of electron-hole pairs by using defective titanium dioxide nanosheets as a carrier and loading Au quantum dots as trapping centers for photogenerated electrons.

[0053] In this invention, the defect-state titanium dioxide nanosheet-supported catalyst can act as a photocatalyst to catalyze the co-conversion of CH4 and CO2 into C2H6 and CO. Furthermore, by controlling the loading of metal particles, the conversion efficiency can be effectively improved. This invention has found that when the mass fraction of Au quantum dots loaded on the support is too low, the conversion efficiency is low; conversely, when the mass fraction of Au quantum dots loaded on the support is too high, the conversion efficiency is also low. Therefore, in this invention, the preferred mass ratio of the support to the metal Au loaded on the support is (95~99.5):(0.5~5), more preferably (95~99):(1~5), including but not limited to 95:5, 95.5:4.5, 96:4, 96.5:3.5, 97:3, 97.5:2.5, 98:2, 98.5:1.5, or 99:1, etc.

[0054] This invention provides a method for preparing the above-mentioned defect-state titanium dioxide supported catalyst, comprising the following steps:

[0055] S1) Titanium dioxide nanosheets and a salt solution of metallic gold are mixed, and the solvent is removed to obtain a mixed powder;

[0056] S2) The above mixed powder is calcined under a hydrogen-argon atmosphere to obtain a defect-state titanium dioxide supported catalyst.

[0057] Preferably, the titanium dioxide nanosheets are prepared according to the following method:

[0058] Titanium dioxide nanosheets were obtained by mixing a titanium source compound and an acidic compound and carrying out a hydrothermal reaction.

[0059] The titanium source compound preferably includes tetrabutyl titanate.

[0060] The acidic compound preferably includes hydrofluoric acid.

[0061] The preferred temperature for the hydrothermal reaction is 160~200℃, more preferably 180~200℃; the preferred time for the hydrothermal reaction is 12~24h, more preferably 20~24h.

[0062] In some specific embodiments of the present invention, the titanium dioxide nanosheets are prepared according to the following method:

[0063] Tetrabutyl titanate and hydrofluoric acid were mixed and subjected to a hydrothermal reaction in a constant temperature oven at 160–200 °C. After the reaction vessel cooled naturally, the mixture was centrifuged and washed multiple times with anhydrous ethanol and deionized water. The resulting nanosheets were then dried in an oven at 80 °C. Preferably, the mixing was carried out in a 50 mL reaction vessel liner using magnetic stirring to ensure thorough mixing. The preferred ratio of tetrabutyl titanate to hydrofluoric acid was 25:1 to 25:4. The preferred drying time was 12–24 h.

[0064] The titanium dioxide nanosheets were then mixed with a salt solution of metallic gold.

[0065] The gold salt solution preferably includes one or more of HAuCl4 solution and NaAuCl4 solution.

[0066] In some specific embodiments of the present invention, step S1) above specifically includes:

[0067] Titanium dioxide nanosheets were mixed and stirred with a salt solution of metallic gold, and then evaporated to dryness at 80-120 °C to obtain a mixed powder.

[0068] The evaporation temperature is more preferably 80~120℃, and even more preferably 100~120℃.

[0069] The resulting mixed powder is then calcined.

[0070] The roasting temperature is preferably 300~500℃, more preferably 400~450℃; the roasting time is preferably 1~2h.

[0071] The heating rate of the roasting is preferably 2~10 ℃ / min, more preferably 2 ℃ / min.

[0072] The hydrogen-argon atmosphere is a mixture of hydrogen and argon, and the volume content of hydrogen is preferably 2% to 20%, more preferably 5%.

[0073] This invention selects a hydrogen-argon atmosphere as the calcination atmosphere. H2 not only reduces the Au ions adsorbed on the titanium dioxide nanosheets to metal quantum dots, but also preferentially excites abundant oxygen vacancies around the metal quantum dots, thus obtaining titanium dioxide nanosheets loaded with Au quantum dots and rich in oxygen vacancies. The hydrogen content affects the size of the formed Au quantum dots and the concentration of the formed oxygen vacancies.

[0074] After the above reaction is completed, the present invention preferably stores the obtained defect-state titanium dioxide nanosheet supported catalyst in a vacuum dryer for subsequent characterization and application.

[0075] In this invention, the point values ​​listed above are merely for listing purposes and are not limited to them. Other point values ​​within their numerical range are also applicable. To avoid complexity, they will not be described in detail.

[0076] The defect-state titanium dioxide nanosheet-supported catalyst provided by this invention is prepared by simple and conventional methods such as hydrothermal reaction and calcination. The operation is simple, the synthesis time is short, and it is convenient for large-scale production. The prepared defect-state titanium dioxide supported catalyst (Au / TiO2-V) o The nanosheets were subjected to UV-Vis diffuse reflectance spectroscopy (UV-vis), static photocurrent measurement, and photoluminescence (PL) measurement. The results show that the Au / TiO2-V nanosheets provided by this invention... o Compared with single TiO2 nanosheet catalysts, the nanosheet catalysts not only show increased light absorption efficiency but also significantly improved separation efficiency of photogenerated carriers and decreased electron-hole pair recombination efficiency. The resulting defect-state titanium dioxide supported catalyst (Au / TiO2-V) o The Au / TiO2-V nanosheets provided in this invention underwent temperature-programmed desorption experiments using CO2 and CH4, which revealed that... o Compared with single TiO2 nanosheet catalysts, the desorption temperatures of CO2 and CH4 are significantly increased by nanosheet catalysts, indicating that the adsorption capacity of CO2 and CH4 is significantly enhanced, which is beneficial to improving the catalytic efficiency of photocatalytic co-conversion of CH4 and CO2.

[0077] Based on this, the present invention provides the application of the above-mentioned defective titanium dioxide supported catalyst or the defective titanium dioxide supported catalyst prepared by the above preparation method as a catalyst for the co-conversion of methane and carbon dioxide.

[0078] This invention addresses the problems of low efficiency and numerous side reactions in the co-conversion of CH4 and CO2 in existing technologies by providing a method for co-converting methane and carbon dioxide, comprising the following steps:

[0079] The defective titanium dioxide supported catalyst described above or the defective titanium dioxide supported catalyst prepared by the above preparation method catalyzes the photocatalytic reaction of methane and carbon dioxide to obtain ethane and carbon monoxide.

[0080] Specifically, the above-mentioned defective titanium dioxide supported catalyst is subjected to photo-irradiation reaction in a flowing mixed atmosphere of CH4 and CO2 to obtain ethane and carbon monoxide.

[0081] The light source for the photoreaction is preferably any one of a xenon lamp, a high-pressure mercury lamp, an LED lamp, or a tungsten iodine lamp, and more preferably a xenon lamp.

[0082] The power of the light source in the photoluminescence reaction is preferably 100-1000 mW / cm². -2More preferably 500-800 mW cm -2 .

[0083] The photoreaction time is preferably 0.5 to 4 hours, more preferably 1 to 2 hours, including but not limited to 1 hour, 1.5 hours or 2 hours.

[0084] The volume ratio of methane to carbon dioxide is preferably 1:19 to 19:1, more preferably 1:1.

[0085] In some embodiments of the present invention, the method for co-converting CH4 and CO2 preferably includes the following steps:

[0086] Weigh an appropriate amount of the above-prepared defective titanium dioxide nanosheet catalyst loaded with Au metal quantum dots, add an appropriate amount of deionized water for ultrasonic dispersion, and then coat it onto a quartz petri dish by drop coating. After drying on a heater, place it in a photocatalytic reactor with openings at both ends, introduce a flowing CH4 and CO2 mixture, and irradiate it with light. In this invention, the photocatalytic reactor can be a gas-solid phase reactor with quartz windows, and the CH4 and CO2 mixture is preferably obtained by mixing high-purity methane (≥99.9%) and high-purity carbon dioxide (≥99.9%) through a gas mixing system.

[0087] Experimental results of photocatalytic co-conversion of CH4 and CO2 show that defect-state titanium dioxide nanosheets loaded with 1.86 wt% Au quantum dots (named Au / TiO2-V) are effective. o Nanosheets were used as a photocatalyst in the photocatalytic co-conversion of CH4 and CO2. After 1.5 h of reaction, 2.6 mmol g of the product was obtained. -1 h -1 The ethane precipitation rate of the TiO2 nanosheets is significantly higher than that of Au-loaded titanium dioxide nanosheets. While single-defect state titanium dioxide nanosheets exhibit good photosensitivity, their visible light capture ability is weak, their photogenerated carrier separation efficiency is poor, and their adsorption and activation abilities for CH4 and CO2 are weak. Pristine TiO2 nanosheets produce almost no ethane.

[0088] To further illustrate the present invention, a detailed description is provided below with reference to embodiments. However, it should be understood that these descriptions are merely for further illustrating the features and advantages of the present invention, and not for limiting the scope of the claims.

[0089] There are no particular restrictions on the source of any raw materials used in this invention; they can be purchased from the market or prepared using conventional methods known to those skilled in the art.

[0090] Example 1

[0091] This embodiment provides an Au / TiO2-V oA method for preparing nanosheet photocatalysts and its application in the photocatalytic co-conversion of CH4 and CO2 to produce ethane:

[0092] Using a pipette, 12.5 mL of tetrabutyl titanate (Sinopharm Chemical Reagent Co., Ltd., purity ≥99%) and 1.5 mL of hydrofluoric acid (Sinopharm Chemical Reagent Co., Ltd., content ≥40%) were transferred separately into a 50 mL reaction vessel liner and stirred for 10 min to ensure thorough mixing. The liner was then placed inside the stainless steel reaction vessel shell, tightened, and placed in a constant temperature oven (Shanghai Jinghong Experimental Equipment Co., Ltd., DHG-9036Y) at 200 °C for 24 h. After natural cooling, the solid obtained from the reaction was collected by centrifugation and washed three times each with ethanol and deionized water. It was then dried overnight in an oven at 80 °C to obtain a dry white powder. 500 mg of the obtained white powder was weighed and dispersed in 20 mL of deionized water. 2 mL of HAuCl4 aqueous solution was added, and the mixture was stirred at 500 rpm for 24 h. The water was then completely evaporated at 100 °C. The resulting powder was thoroughly ground, and then heated from room temperature to 400 °C at a rate of 2 °C / min under a 5% H2 / Ar environment, and held for 1 h to obtain a purple powder sample, Au / TiO2-V. o Nanosheets.

[0093] The obtained Au / TiO2-V o The nanosheets were characterized using X-ray powder diffraction (Philips X'Pert Pro Superdiffractometer), high-resolution transmission electron microscopy (JEOL-2010 TEM), X-ray photoelectron spectroscopy (ESCALAB250), and electron paramagnetic resonance spectroscopy (JEOL JES-FA200). The mass fraction of Au was determined using inductively coupled plasma atomic emission spectrometry (ICP-AES) (measured to be 1.86%). The obtained XRD diffraction patterns are shown below. Figure 1 As shown, the scanning transmission electron microscope (STEM) image and the corresponding particle size distribution map are as follows: Figure 2 As shown in the ab diagram, the element distribution is as follows: Figure 3 As shown, the X-ray photoelectron photoelectron spectrum (XPS) is as follows: Figure 4 As shown, the obtained paramagnetic resonance (EPR) spectrum is as follows: Figure 5 As shown, atomic force probe microscopy (AFM) images and corresponding height distribution maps are as follows. Figure 6 The above characterization shows that Au quantum dots are uniformly dispersed on titanium dioxide nanosheets with abundant oxygen vacancies.

[0094] Comparative Example 1

[0095] 12.5 mL of tetrabutyl titanate (Sinopharm Chemical Reagent Co., Ltd., purity ≥99%) and 1.5 mL of hydrofluoric acid (Sinopharm Chemical Reagent Co., Ltd., content ≥40%) were respectively transferred into the liner of a 50 mL reaction vessel and stirred for 10 min to ensure thorough mixing. The liner was then placed inside the stainless steel reaction vessel shell, tightened, and placed in a constant temperature oven (Shanghai Jinghong Experimental Equipment Co., Ltd., DHG-9036Y) at 200 °C for 24 h. After natural cooling, the solid obtained from the reaction was collected by centrifugation and washed three times each with ethanol and deionized water. It was then dried overnight in an oven at 80 °C to obtain a dry white powder, which was TiO2 nanosheets.

[0096] The obtained TiO2 nanosheets were characterized using X-ray powder diffraction (Philips X'Pert Pro Superdiffractometer), high-resolution transmission electron microscopy (JEOL-2010 TEM), X-ray photoelectron spectroscopy (ESCALAB250), and electron paramagnetic resonance spectroscopy (JEOL JES-FA200). The obtained XRD diffraction patterns are shown below. Figure 1 As shown, the transmission electron microscope (TEM) image is as follows: Figure 7 As shown in Figure a, the high-resolution transmission electron microscope image is as follows: Figure 8 As shown, the X-ray photoelectron photoelectron spectrum (XPS) is as follows: Figure 4 As shown, the obtained paramagnetic resonance (EPR) spectrum is as follows: Figure 5 As shown above, comparative example 1 successfully synthesized oxygen-vacancy-free titanium dioxide nanosheets.

[0097] Comparative Example 2

[0098] 12.5 mL of tetrabutyl titanate (Sinopharm Chemical Reagent Co., Ltd., purity ≥99%) and 1.5 mL of hydrofluoric acid (Sinopharm Chemical Reagent Co., Ltd., content ≥40%) were pipetted into the liner of a 50 mL reaction vessel and stirred for 10 min to ensure thorough mixing. The liner was then placed inside the stainless steel reaction vessel shell, tightened, and placed in a constant temperature oven (Shanghai Jinghong Experimental Equipment Co., Ltd., DHG-9036Y) at 200 ℃ for 24 h. After natural cooling, the solid obtained from the reaction was collected by centrifugation and washed three times each with ethanol and deionized water. It was then dried overnight in an oven at 80 ℃ to obtain a dry white powder. 100 mg of the white powder was weighed and dispersed in 100 mL of deionized water by ultrasonication. 0.4 mL of HAuCl4 aqueous solution was added, and the mixture was stirred at 500 rpm for 24 h. Freshly prepared sodium borohydride solution was then added dropwise, and the solid obtained was collected by centrifugation and washed three times with water. After drying in an oven at 80 ℃ overnight, the resulting pink solid powder was Au / TiO2 nanosheets.

[0099] The obtained Au / TiO2 nanosheets were characterized using X-ray powder diffraction (Philips X'Pert Pro Superdiffractometer), high-resolution transmission electron microscopy (JEOL-2010 TEM), X-ray photoelectron spectroscopy (ESCALAB250), and electron paramagnetic resonance spectroscopy (JEOL JES-FA200). The mass fraction of Au was determined by inductively coupled plasma atomic emission spectrometry (ICP-AES) (1.89%). The obtained XRD diffraction patterns are shown below. Figure 1 As shown, the transmission electron microscope (TEM) image is as follows: Figure 7 As shown in Figure b, the X-ray photoelectron photoelectron spectrum (XPS) is as follows: Figure 4 As shown, the obtained paramagnetic resonance (EPR) spectrum is as follows: Figure 5 As shown above, Au quantum dots are uniformly dispersed on oxygen-vacant titanium dioxide nanosheets.

[0100] Optical property characterization

[0101] Static photocurrent testing: Au / TiO2 nanosheets prepared in Comparative Example 2 and Au / TiO2-V prepared in Example 1 o Taking nanosheets as an example, 5 mg of Au / TiO2 nanosheets and Au / TiO2-V were weighed out respectively. oNanosheets were added to 2 mL of ethanol and sonicated for 10 min. 300 μL of the dispersion was then drop-coated onto a 2 cm × 1 cm FTO conductive glass substrate (drop-coating area 1 cm × 1 cm) and dried under an infrared lamp. Photocurrent was then measured using a Zahner electrochemical workstation (Zahner PP211) with 0.5 mol / L Na₂SO₄ solution as the electrolyte. A three-electrode system was used: a carbon rod as the counter electrode, a silver chloride electrode as the reference electrode, and ITO glass as the working electrode. The test results are as follows: Figure 9 .

[0102] Combining the Au / TiO2 nanosheets prepared in Comparative Example 2 and the Au / TiO2-V prepared in Example 1 o Surface photovoltage (SPV) and photoluminescence (PL) spectroscopy measurements were performed on nanosheets, such as... Figure 10 and Figure 11 It can be seen that compared to defect-free Au / TiO2 nanosheets, Au / TiO2-V o It exhibits high photogenerated carrier separation efficiency and effectively suppresses the rebinding of photogenerated carriers.

[0103] The pure TiO2 nanosheets prepared in Comparative Example 1, the Au / TiO2 nanosheets prepared in Comparative Example 2, and the Au / TiO2-V nanosheets prepared in Example 1 are compared. o The nanosheets were characterized by UV-Vis and near-infrared diffuse reflectance (UV-vis) spectroscopy, and the results are as follows: Figure 12 .Depend on Figure 12 It is known that the surface plasmon resonance effect of Au enhances the absorption of the catalyst in the light-sensitive region (400-800 nm). Enhanced light absorption is beneficial to improving the separation efficiency of photogenerated carriers, thereby improving catalytic activity.

[0104] Characterization of CO2 and CH4 adsorption capacity

[0105] Comparison of Au / TiO2 nanosheets prepared in Comparative Example 2 and Au / TiO2-V prepared in Example 1 o The nanosheets were subjected to temperature-programmed desorption (CO2-TPD) tests for CO2 and CH4, respectively, and the results are as follows: Figure 13 and Figure 14 As shown. Au / TiO2-V o The nanosheets exhibited higher CO2 and CH4 desorption temperatures than Au / TiO2 nanosheets, demonstrating that Au / TiO2-V o The nanosheets exhibit excellent adsorption capacity for both CO2 and CH4, which lays the foundation for achieving co-conversion of CO2 and CH4.

[0106] In addition, the Au / TiO2 nanosheets prepared in Comparative Example 2 and the Au / TiO2-V prepared in Example 1 were compared. o Theoretical simulations of CO2 adsorption on nanosheets revealed that CO2 is adsorbed on Au / TiO2-V o At the nanosheet metal-support interface, the C and O molecules in CO2 can bond with electron-rich Au and electron-deficient Ti, respectively, greatly enhancing CO2 adsorption. For example... Figure 15 Au / TiO2-V o It exhibits an extremely low CO2 adsorption energy of -0.54 eV, and the enhanced adsorption capacity of the reactants is beneficial to increasing the catalytic efficiency.

[0107] Photocatalytic application example: Photocatalytic co-conversion of CH4 and CO2 to produce ethane

[0108] Take 10 mg of pure TiO2 nanosheets prepared in Comparative Example 1, Au / TiO2 nanosheets prepared in Comparative Example 2, and Au / TiO2-V nanosheets prepared in Example 1, respectively. o Nanosheets were added to 3 mL of deionized water and ultrasonically dispersed. The resulting dispersion was drop-coated onto a quartz dish and dried at 70 °C on a heater. The dried quartz dish was then transferred to the bottom of the Zhongjiao Jinyuan photocatalytic reactor. High-purity Ar gas was first introduced at a total flow rate of 20 mL / min and maintained for 30 min to remove air and other impurities adsorbed on the catalyst surface. Then, the Ar gas was converted to high-purity CO2 at a flow rate of 10 mL / min and high-purity CH4 at a flow rate of 10 mL / min. The two gases were mixed through a gas mixing system and then introduced into the photocatalytic reactor. A 300 W Xe lamp (CEL-HXF300, Beijing Zhongjiao Jinyuan Technology Co., Ltd.) was used as the light source. The gas obtained after the reaction was collected using a gas collection bag and then injected into a gas chromatograph for quantification (Agilent GC-7890B equipped with a TDX-01 column, thermal conductivity detector (TCD), and flame ionization detector (FID)).

[0109] TiO2 nanosheets in Comparative Example 1, Au / TiO2 nanosheets in Comparative Example 2, and Au / TiO2-V in Example 1 o The product distribution diagram of the photocatalytic co-conversion of CH4 and CO2 by nanosheets is shown below. Figure 16 .from Figure 16 As can be seen, TiO2 nanosheets produce almost no ethane, while Au / TiO2 nanosheets exhibit a higher C2H6 precipitation rate, indicating that the supported Au species are beneficial for driving C2H6 formation. The Au / TiO2-V obtained in this invention... o The nanosheets further improved the ethane precipitation rate to 2.6 mmol g. -1 h -1This is approximately three times that of Au / TiO2 nanosheets. Furthermore, a significant increase in the CO product precipitation rate was observed, suggesting that the introduced oxygen vacancies enhanced CO2 adsorption and activation. The effect of Au mass fraction on the ethane formation rate was then further investigated. Figure 17 The precipitation rate of C2H6 exhibits a volcanic trend with increasing Au mass fraction, reaching its highest point at an Au mass fraction of 1.86%. Further increases in Au mass fraction lead to a significant decrease in the ethane precipitation rate, likely due to excessive Au quantum dots obscuring the TiO2 substrate and reducing light absorption. Therefore, controlling the Au loading between 1% and 3% yields C2H6 products with higher precipitation rates.

[0110] Furthermore, to identify the sources of C2H6 and CO in the product, isotope labeling experiments were performed, and the product was detected using synchrotron ultraviolet photoionization mass spectrometry. Figure 18 ,use 13 C-labeled CH4 and unlabeled CO2 were used as reactants to obtain... 13 C-mark 13 The presence of C2H6 and some of its fragment peaks, along with unlabeled CO, indicates that the C2H6 in the product originates from the oxidation of CH4, while the CO in the product originates from the reduction of CO2.

[0111] Based on the above embodiments and comparative examples, using the Au quantum dot-supported defective titanium dioxide nanosheets prepared in this invention as a photocatalyst, high-performance simultaneous conversion of CH4 and CO2 into valuable fuels can be achieved. CH4 and CO2 can be converted by interacting with photogenerated holes and electrons generated by the photocatalyst, respectively. Spectroscopic tests show that the metal-supported defective titanium dioxide nanosheets have stronger light absorption capacity and electron-hole separation efficiency, thus exhibiting excellent photocatalytic properties. Furthermore, the defective titanium dioxide-supported catalyst has stronger CH4 and CO2 adsorption capacity, laying the foundation for achieving simultaneous conversion of CH4 and CO2. This invention provides valuable guidance for exploring the preparation of high-performance photocatalysts for the co-conversion of CH4 and CO2.

[0112] The above description of the embodiments is only for the purpose of helping to understand the method and core ideas of the present invention. It should be noted that those skilled in the art can make several improvements and modifications to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the protection scope of the claims of the present invention.

Claims

1. Application of defect-state titanium dioxide supported catalysts as catalysts for the co-conversion of methane and carbon dioxide to produce ethane and carbon monoxide; The defect-state titanium dioxide supported catalyst includes a support and metal Au supported on the surface of the support; The carrier is a defective titanium dioxide nanosheet with oxygen vacancies.

2. The application according to claim 1, characterized in that, The loading of the metal Au is 1% to 3%.

3. The application according to claim 1, characterized in that, The thickness of the defective titanium dioxide nanosheets is 3~5 nm; The average particle size of the metal Au is 1~8 nm.

4. The application according to claim 1, characterized in that, The preparation method of the defect-state titanium dioxide supported catalyst includes the following steps: S1) Titanium dioxide nanosheets and a salt solution of metallic gold are mixed, and the solvent is removed to obtain a mixed powder; S2) The above mixed powder is calcined under a hydrogen-argon atmosphere to obtain a defect-state titanium dioxide supported catalyst.

5. The application according to claim 4, characterized in that, The titanium dioxide nanosheets were prepared according to the following method: Titanium dioxide nanosheets were obtained by mixing a titanium source compound and an acidic compound and carrying out a hydrothermal reaction.

6. The application according to claim 5, characterized in that, The titanium source compound includes tetrabutyl titanate; The acidic compound includes hydrofluoric acid; The hydrothermal reaction temperature is 160~200℃; the hydrothermal reaction time is 12~24h.

7. The application according to claim 4, characterized in that, The salt solution of metallic gold includes one or more of HAuCl4 solution and NaAuCl4 solution; The roasting temperature is 300~500℃; the roasting time is 1~2 hours; The heating rate of the calcination is 2~10 ℃ / min; The hydrogen-argon atmosphere is a mixture of hydrogen and argon, with a hydrogen volume content of 2% to 20%.

8. A method for co-converting methane and carbon dioxide, characterized in that, Includes the following steps: A defect-state titanium dioxide supported catalyst was used to catalyze the photocatalytic reaction of methane and carbon dioxide to obtain ethane and carbon monoxide; The defect-state titanium dioxide supported catalyst includes a support and metal Au supported on the surface of the support; The carrier is a defective titanium dioxide nanosheet with oxygen vacancies.

9. The method according to claim 8, characterized in that, The light source for the photoreaction is selected from any one of xenon lamps, high-pressure mercury lamps, LED lamps, or tungsten iodine lamps; The power of the light source in the photoluminescence reaction is 100-1000 mW / cm². -2 ; The photoreaction time is 0.5~4 h; The volume ratio of methane to carbon dioxide is 1:19 to 19:1.

Citation Information

Patent Citations

  • Gold nano-particle / titanium dioxide nano-flower composite material, preparation method thereof and application of composite material

    CN108579738A

  • Monoatomic catalyst, and preparation method and applications thereof

    CN110327920A